Does co-operation affect positively innovative performance? Case study of Estonia and Romania - Prokop, Viktor; Amponsah Odei, Samuel; Stejskal, Jan (Marketing & Menedzsment, 2017)
AIMS OF THE PAPER SMEs support their innovative processes with connecting to networks (corporate or business or knowledge-based or cooperative). Many international studies show that participation in the cooperative network can help to improve the innovation performance of small or medium sized enterprises. It has been proved that various types of cooperative linkages (e. g. inter-firm cooperation and cooperation with the intermediaries, cooperation with research organizations or cooperation in the holding group) has a positive impact on the firm’s ability to innovate. An interesting question is the involvement of government or public institution in these cooperative networks. Mostly the world wide studies show that their involvement does not bring significant positive benefits. But the new forms of cooperation, such as vertical or horizontal cooperation with customers and suppliers or competing companies also play a significant role in the innovation processes. Even some studies show that the cooperation among the industrial enterprises and customers is more important than cooperation in the knowledge-based network. The question remains whether the results of various international studies are also valid in the CEE regions. THE METHODOLOGY Therefore, to fill the gap, we analyse the influence of cooperation with different partners (e. g. customers, competitors, universities) on the growth of firms' turnover from innovated products in manufacturing industries (in total, 4903 firms) in Estonia and Romania between the years 2010-2012 by using own multiple linear regression models. For data collection, we use CIS, which is a harmonised questionnaire. THE MOST IMPORTANT RESULTS Results show, that proper selection of cooperation partners (especially in Estonia) in combination with other determinants of innovative activities (e. g. participation in the group of companies, public financing) lead to creation of synergies and spillover effects, that significantly influence innovative activities. RECOMMENDATION We recommend countries to thoroughly define their innovation policy goals and system of support to analyse them before their wide application.